If it's not what You are looking for type in the equation solver your own equation and let us solve it.
54.6=6(m+2.4)
We move all terms to the left:
54.6-(6(m+2.4))=0
We calculate terms in parentheses: -(6(m+2.4)), so:We get rid of parentheses
6(m+2.4)
We multiply parentheses
6m+14.4
Back to the equation:
-(6m+14.4)
-6m-14.4+54.6=0
We add all the numbers together, and all the variables
-6m+40.2=0
We move all terms containing m to the left, all other terms to the right
-6m=-40.2
m=-40.2/-6
m=6+1.9090909090909/2.7272727272727
| 1/5p+-8=-5 | | 1/2(5z-7)=2z+2 | | 5=5(4n-1)÷3 | | 10y=Y+81 | | 1/2(2x+6)=3x13 | | 2(x-1)=-4x-2+6x | | (X-9)(x+3)=x^2+4x+13 | | 8+15x=128-5x | | 1/2x+2/5x=90 | | 3-3=2x+11 | | -m/8-12=-3 | | 21n^2+69n-60=0 | | 3y+6=3y+5 | | 8x-5-3x=5-10 | | 4n+7=81 | | 6y+60=90 | | 8=9k+12+7k | | Y+4x+37=180 | | 2(x-10)=3(x-9) | | 6x+14-3x=9- | | 1/2(2x-8)+x-2=2(x-3) | | 5-t/3t=12 | | 11x-1=10x+10 | | 2(3x-10)=17 | | 9(-9)+16=x | | 5x+6=8x=13 | | -7x+12+-8x+48=180 | | x+13+2x-7=180 | | 8/19y+56=0 | | 2x+3-8x=14+2x-1 | | -3f−5=-2f+5 | | 16-8-3x=-13 |